Selective Recovery of Gold from Electronic Waste Using 3D-Printed Scavenger - Lahtinen, Elmeri (ACS Omega, 2017)
[Image: see text] Around 10% of the worldwide annual production of gold is used for manufacturing of electronic devices. According to the European Commission, waste electric and electronic equipment is the fastest growing waste stream in the European Union. This has generated the need for an effective method to recover gold from electronic waste. Here, we report a simple, effective, and highly selective nylon-12-based three-dimensional (3D)-printed scavenger objects for gold recovery directly from an aqua regia extract of a printed circuit board waste. Using the easy to handle and reusable 3D-printed meshes or columns, gold can be selectively captured both in a batch and continuous flow processes by dipping the scavenger into the solution or passing the gold-containing solution through the column. The possibility to optimize the shape, size, and flow properties of scavenger objects with 3D printing enables the gold scavengers to match the requirements of any processing plants.